2011
DOI: 10.3109/15412555.2011.558546
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Sputum Production on Respiratory Symptoms in Severe COPD

Abstract: Increased sputum production in severe COPD is frequently encountered daily and is associated with more respiratory symptoms, worse airflow obstruction, and less emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…When we look for number of patients having more than one exacerbation in previous years, studies show that exacerbation was found more in smoker group than non-smoker which is similar to other studies. 12 None of the patients in our study had malnutrition (BMI<20), but it was found lower for smoker COPD than non-smoker COPD which is in line with other studies. 13 Our studies shows that severe & very severe COPD was more prevalent in non-smoker when compared to smoker but moderate COPD was more frequent in smoker group.…”
Section: Resultssupporting
confidence: 92%
“…When we look for number of patients having more than one exacerbation in previous years, studies show that exacerbation was found more in smoker group than non-smoker which is similar to other studies. 12 None of the patients in our study had malnutrition (BMI<20), but it was found lower for smoker COPD than non-smoker COPD which is in line with other studies. 13 Our studies shows that severe & very severe COPD was more prevalent in non-smoker when compared to smoker but moderate COPD was more frequent in smoker group.…”
Section: Resultssupporting
confidence: 92%
“…In a telemedicine study of 50 patients with severe COPD with more than 14,500 observation days, those who complained of more sputum symptoms on a daily basis also complained of more dyspnea, cough, wheeze, and nasal congestion and had lower peak flow measurements (69). Compared with subjects without CB, GOLD stage 2 to 4 subjects with CB symptoms in the COPDGene cohort also had more severe dyspnea, more allergic nasal and ocular symptoms, more frequent nocturnal awakenings by cough and dyspnea, and worse St. George's Respiratory Questionnaire disease-specific quality of life scores (6).…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…It is difficult for some patients with severe to very severe AECOPD to expel sputum, necessitating respiratory support (Kim et al, 2011). Sputum-based longitudinal airway microbiome studies have been performed for the deep exploration of therapeutic targets and the development of improved treatment options (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As symptoms progress, patients experience severe shortness of breath and extreme dyspnea. This makes the collection of sputum samples challenging (Kim et al, 2011), as sputum examination requires the use of a high-permeability 5% saltwater spray, and patients often find it difficult to tolerate atomization, resulting in failure to induce sputum production for sampling. According to the World Health Organization, COPD will become the third most common cause of death globally by 2020 and will be the fifth most economically burdensome disease.…”
Section: Introductionmentioning
confidence: 99%